The Influence of Service Quality, Shop Atmosphere and Word of Mouth on Purchasing Decisions at Coffee Shops Such as Lenteng Agung South Jakarta City - Gadis Dwi Inanta; Kumba Digdowiseiso; Elwisam (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of service quality. Shop atmosphere, word of mouth on purchasing decisions at coffee shops for example. The data source for this research uses primary data in the form of a questionnaire. The research data was given to 96 respondents who had purchased at a coffee shop, for example, with statistical data analysis methods using IBM SPSS Statistics version 25 software. The results of this study showed that there was no positive and significant effect of variable X1 on Y while variables X2 and X3 have a positive and significant influence on Y. There is no effect of the service quality variable (X1) on the purchasing decision variable (Y), which means that the presence or absence of the service quality variable will not affect the purchasing decision at the Seumpama Coffee Shop. While the store atmosphere variable (X2) and word of mouth variable (X3) have a positive and significant influence on the purchasing decision variable (Y). That means the better the atmosphere of the shop and word of mouth, the higher the purchase decision at Seumpama Coffee Shop.